Efektivitas Penggunaan Cerita Anak Dalam Mengembangkan Kreativitas Menggambar Siswa SD Di Kecamatan Banawa Kabupaten Donggala - Langgadesa, Yun Ratna; Mursak, Muliati; Inayah, Faidhul (Jurnal Kreatif Online, 2020)
The teacher's lack of artistic skills and examples of drawings that students can see results in students' images limited to the pictures of mountains, trees, houses, or cheating on books and pictures displayed in the classroom. This research tries to see the effectiveness of using stories as a solution to develop creativity both in finding new creative ideas and new drawing objects in elementary school. This research was classroom action research. The results showed that the average score of learning outcomes in cycle I was 47 and increased in cycle II to 83. The effectiveness of learning increased from cycle I to cycle II, as seen from the 4 assessment indicators. From the results of the study, it can be concluded that the implementation of learning the art of drawing using stories in grade IV students at SDN 2 Banawa can increase the effectiveness of learning which can be seen from the achievement of learning objectives. In addition, the implementation of learning to draw using stories as a drawing idea using an inspirational approach in grade 4th SDN 2 Banawa can improve students' creativity in finding new objects in pictures.Â